A projection of primary knee replacement in Denmark from 2020 to 2050 - Daugberg, Louise; Jakobsen, Thomas; Nielsen, Poul Torben; Rasmussen, Mathias; El-Galaly, Anders (Acta Orthopaedica, 2021)
Background and purpose — The incidence of knee replacements (KRs) has increased in the past decades. Previous studies have forecast a continuous and almost exponential rise in the use of KRs, but this rise must cease at some point. We estimated when and at what incidence the use of KRs will plateau in Denmark. Patients and methods — We retrieved 138,223 primary KRs conducted from 1997 to 2019 from the Danish Knee Arthroplasty Registry. Censuses from 1997 to 2019 as well as population projections from 2020 through 2050 were collected from Statistics Denmark. We applied logistic and Gompertz regression analysis to the data to estimate the future incidence until 2050 with root mean squared error (RMSE) as a quantitative measurement of the models’ fit. Results — The Danish incidence of KRs from 1997 to 2009 increased by more than 300%, but has stalled since 2009. Logistic and Gompertz regression had an RMSE of 14 and 15 indicating that these models fitted the data well. Logistic and Gompertz regressions estimated that the maximum incidence will be reached in 2030 at 250 (95% prediction interval [PI]) 159–316) KRs per 105 or in 2035 at 260 (PI 182–336) KRs per 105, respectively. Interpretation — The Danish incidence of KRs seems set to plateau within the coming decades. Countries experiencing a current exponential rise at a lower incidence may benefit from this study’s projection when forecasting their future demand for KRs.